Variable Thermal Comfort Index for Indoor Work Space in Office Buildings: A Study in Germany - Kuchen, Ernesto (2016)
International standards state the thermal comfort requirements that office spaces must comply with. These are based on a model developed by Prof. Paul Ole Fanger of the Centre for Indoor Environment and Energy, Denmark. Today, forty-year research shows an evolution in these experiences. The work presented here is to develop a tool to evaluate the thermal comfort of working environments of office buildings. A methodology is devised on the basis of on-site measurements and questionnaire responses. For measurements, a mobile unit equipped with sensors is used, whereas the questionnaire obtains user responses on thermal quality of the work space. The thermal conditions of thirty office buildings presenting different acclimatization systems have been surveyed. The correlation between objective and subjective data allows developing a formula that shows the thermal comfort level for a given environment as a function of local aspects. For the surveyed buildings, the resulting comfortable temperature was 23.3˚C, and the minimum percentage of user individuals experiencing discomfort with such temperature was 7%.